(untitled) (LEARNing Landscapes, 2009)
In this article, I explore the process of transmediation by examining selected art conversations—nonverbal communication made through painting—and poetry that urban fifth graders composed in response to a query about how they learn. Specifically, I examine three students’ works, noting how the use of multiple symbol systems helped each to compose strong visual and written texts. In studying the work the students composed, I conclude that visual art and poetry make fine partners in intellectual endeavors aimed at educating the imagination.